Fiscal divergence, current account and TARGET2 imbalances in the EMU - José Abad; Axel Löffler; Gunther Schnabl; Holger Zemanek (Universität Leipzig, Wirtschaftswissenschaftliche Fakultät, 2012)
The paper scrutinizes the reasons for the European debt crisis, the implications for TARGET2 imbalances and options for surplus liquidity absorption within an asymmetric EMU. It is argued that starting from the turn of the millennium diverging fiscal policy paths and diverging unit labour costs were the driving force of rising intra-European current account imbalances within the euro area, which were enhanced by post-2001 low interest rate policies and changing financing conditions for the German banking sector. The paper shows how since the outbreak of the crisis the adjustment of intra-EMU current account imbalances is postponed by a rising divergence of TARGET2 balances, as the repatriation of private international credit and deposit flight from the crisis economies is substituted by central bank credit. Given that this process has brought Deutsche Bundesbank into a debtor position to the domestic financial system, we discuss options for liquidity absorption by Deutsche Bundesbank to forestall asset price bubbles in Germany.
Keywords: 330; EMU; fiscal divergence; TARGET2; current account imbalances